Relationship between work-family conflict and unhealthy eating: Does eating style matter?. (1st April 2018) - Shukri, Madihah; Jones, Fiona; Conner, Mark
Abstract: There is increasing evidence to suggest that work–family conflict is implicated in poor eating patterns. Yet, the underlying mechanism remains unexplored. The objectives of the present study were to demonstrate the interplay between work–family conflict, eating style, and unhealthy eating, and to test whether body mass index (BMI) and its interactions further explicate the relationships. In this study, 586 Malaysian adults (normal weight n = 437, overweight n = 149) completed a questionnaire, which included demographic variables, work–family scales, eating style measures, namely, restrained, emotional or external eating and reported food intake. As hypothesized, results showed that family-to-work conflict (FWC), emotional eating and external eating were positively related to unhealthy food consumption. In addition, emotional eating was found to moderate the impact of FCW on eating. These findings are consistent with research that has revealed emotional eating can indeed increase the positive association between stress such as conflict and unhealthy food choices. However, we found no clear support for the interactive effects of BMI. Our research builds on the findings of existing research as it demonstrates the role of eating style in explaining the association between work–family conflict and unhealthy eating. This conclusion has potential implications for appropriate interventions and calls for the enhancement of various policies to tackle obesity and other health problems.